ATTITUDE OF THE PH.D RESEARCH SCHOLARS OF DIBRUGARH UNIVERSITY TOWARDS USING WEB-BASED INFORMATION RESOURCES - Hazarika, Drishti; Chaliha, Asomi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The web-based information resources are any kind of information resources that are received from various websites in the form of verbal, non-verbal, pictorial, auditory, written, video, podcasts, documentaries, movie, e-books etc. The necessity of web-based information resources is felt not only by students and academicians and scholars but by every human on earth, this is because of its easily accessible and “create and share” nature. The educational institutions of all levels are seen accessing and relying upon these web-based information resources. The Ph.D. research scholars are seen using the web-based information resources in abundance for their research purpose. Thus, this study prioritizes to find out the difference between male and female Ph.D. research scholars of Dibrugarh University in their attitude towards using web-based information resources and difference among Arts, Commerce, Science stream Ph.D. research scholars of Dibrugarh University in their attitude towards using web-based information resources. The researcher found that there was no difference between Male and Female Ph.D. Research Scholars of Dibrugarh University in their attitude towards using Web-Based Information resources. There is a significant difference in the attitude of the Arts and Science Stream Ph.D. Research Scholars towards using Web –Based Information Resources. There is a significant difference in the attitude of the Arts and Commerce Stream Ph.D. Research Scholars towards using Web –Based Information Resources. Whereas, there is no significant difference in the attitude of the Science and Commerce Stream Ph.D. Research Scholars towards using Web –Based Information Resources.